Analisis Kandungan Boraks (Natrium Tetraborate) Pada Kerupuk Yang Beredar di Pasar Besar Kota Palangka Raya - Noor Sulaiman, Reza; Augustina, Indria; Ratnasari, Arini; Immanuela Toemon, Agnes; Nugrahini, Sintha (Fakultas Kedokteran, Universitas Palangka Raya, 2024)
The addition of Food Additives containing chemical active substances has been widely used in daily life. Many food producers still use them as hazardous food additives that can lead to health problems. This study aims to determine the presence of borax and measure the levels found in unbranded crackers sold in the Palangka Raya City Main Market. This research is a descriptive study with a cross-sectional design. The research sample consisted of 41 unbranded crackers sold in the Palangka Raya City Main Market, selected using a sampling technique with total sampling based on inclusion and exclusion criteria. The research instruments used were the borax easy kit test and sp-300 spectrophotometer. Data processing techniques used descriptive analysis with data presentation in the form of percentage values. The results of this study identified borax in 41 samples of unbranded crackers sold in the Palangka Raya City Main Market, with 4 samples containing borax in each coriander cracker sample. Sample 1 was found to contain 37.74 grams of borax, sample 2 contained 33.62 grams of borax, sample 4 contained 61.63 grams of borax, and sample 7 contained 15.57 grams of borax.